2018
DOI: 10.1007/978-981-13-2820-6_2
|View full text |Cite
|
Sign up to set email alerts
|

The Twin Track Model of Employee Voice: An Anglo-American Perspective on Union Decline and The Rise of Alternative Forms of Voice

Abstract: Any opinions expressed here are those of the author(s) and not those of the UCL Institute of Education. Research published in this series may include views on policy, but the institute itself takes no institutional policy positions. DoQSS Workings Papers often represent preliminary work and are circulated to encourage discussion. Citation of such a paper should account for its provisional character. A revised version may be available directly from the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In terms of the mechanisms by which commitment-led HR improves productivity there is suggestive evidence that it accrues through employee engagement and through improvements in workers' well-being. One study has identified a causal linkage between individual worker happiness and individual productivity (Oswald et al, 2015) while other recent studies suggest this link also exists at an organizational level (Bryson, Forth and Stokes, 2017;Bryson, Freeman, Gomez and Willman, 2017;.…”
Section: Employee Satisfaction: the Role Of Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the mechanisms by which commitment-led HR improves productivity there is suggestive evidence that it accrues through employee engagement and through improvements in workers' well-being. One study has identified a causal linkage between individual worker happiness and individual productivity (Oswald et al, 2015) while other recent studies suggest this link also exists at an organizational level (Bryson, Forth and Stokes, 2017;Bryson, Freeman, Gomez and Willman, 2017;.…”
Section: Employee Satisfaction: the Role Of Management Practicesmentioning
confidence: 99%
“…With our full set of controls and typically "hard-to-observe" worker attitudes added to standard multivariate analyses, the relationship between unionization and employee satisfaction is expected to turn positive. Interestingly, the new empirical studies establishing neutral or positive associations between unions and employee satisfaction have appeared at the tail end of a steep decline in the number of workers covered by collective agreements in Britain (Bryson, Freeman, Gomez and Willman, 2017). And yet, British employers appear to still value worker input into decision making processes, as evidenced by the fact that since the early 1980s the percentage of workplaces (and workers) with some formal mechanisms for employees to express their voice has remained steady at around 80 percent (Willman et al, 2006;Bryson and MacKerron, 2016).…”
mentioning
confidence: 99%
“…Union locals in the United States are reliant on the recruitment and retention of members (their customers) as their primary income source. 3 To do so they must organise employees under the Wagner Act by winning majority support among employees in the same bargaining unit and efficiently servicing those members through the provision of union membership (Bryson et al, 2019).…”
Section: The Market For Union Membershipmentioning
confidence: 99%
“…With our full set of controls and typically 'hard-to-observe' worker attitudes added to standard multivariate analyses, the relationship between unionisation and employee satisfaction is expected to turn positive. Interestingly, the new empirical studies establishing neutral or positive associations between unions and employee satisfaction have appeared at the tail end of a steep decline in the number of workers covered by collective agreements in Britain (Bryson, Freeman, Gomez and Willman, 2017). And yet, British employers appear to still value worker input into decision making processes, as evidenced by the fact that since the early 1980s the percentage of workplaces (and workers) with no formal mechanisms for employees to express their voice has remained steady at around 20 percent (Willman et al, 2006;Bryson, 2017).…”
Section: Employee Satisfaction: the Role Of Union And Non-union Worker Voicementioning
confidence: 99%